2005
DOI: 10.1097/01.bpo.0000150809.28171.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the Multiplier Method for Predicting Limb Length at Maturity, Part I

Abstract: To validate the accuracy of the multiplier method in predicting bone and limb maturity lengths, radiographs of 60 patients treated for lower limb length discrepancy were measured. Longitudinal limb length data were used to predict maturity lengths of non-epiphysiodesed normal bones and short bones. Mean errors for predictions were 1.1 cm (SD = 0.9) and 1.5 cm (SD = 1.3) for the multiplier method using chronologic age and skeletal age, respectively. Regression correlation values between multiplier method predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 16 publications
1
30
1
Order By: Relevance
“…The results of the present study are similar to that of Aguilar et al [1,2], who noted that the multiplier method erred as much as 4.4 cm when predicting adult heights for boys and 2.6-cm for girls 5-years-old and younger. Another study by Sanders et al [8] showed that use of the multiplier method can cause errors as great as 5 cm when used in patients who already had their growth spurt.…”
supporting
confidence: 81%
“…The results of the present study are similar to that of Aguilar et al [1,2], who noted that the multiplier method erred as much as 4.4 cm when predicting adult heights for boys and 2.6-cm for girls 5-years-old and younger. Another study by Sanders et al [8] showed that use of the multiplier method can cause errors as great as 5 cm when used in patients who already had their growth spurt.…”
supporting
confidence: 81%
“…8 Furthermore, one does not have to determine a patient's growth percentile or skeletal age to use the multipliers. The multiplier method was recently shown to be more accurate 9 Using the same data, 5 we calculated an upper-extremity bone multiplier that can be applied to limb-length discrepancy prediction, timing of epiphysiodesis, and growth-remaining determination for the humerus, radius, and ulna. The multiplier can be applied to cases of congenital (eg, radial clubhand, congenital ulnar dysplasia, hemihypertrophy) or developmental (eg, Ollier's disease, poliomyelitis, growth arrest, multiple hereditary exostoses) upper-limb-length discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies 9,10 showed that the multiplier method is a simpler and more accurate method of lower-limb-length and epiphysiodesis prediction than are the methods of Moseley 2 and Anderson et al 1,11 The purpose of this study was not only to develop similar multipliers for the upperlimb bones and show that the multiplier method is percentile independent but also to determine it is independent of race, nationality, and generation.…”
Section: And Bortel and Pritchettmentioning
confidence: 98%
See 1 more Smart Citation
“…Aguilar et al found that the Moseley method is as accurate as the multiplier method in predicting bone maturity lengths but less accurate in predicting limb length discrepancies at maturity after epiphyseodesis [26,27]. Dewaele and Fabry were not able to significantly improve their results in timing the skeletal age for epiphyseodesis by using the Moseley straight-line graph, and their principal source of error was in estimating the bone age [3].…”
Section: Discussionmentioning
confidence: 99%